2006
DOI: 10.4049/jimmunol.177.12.8684
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 Restores Immunity to Mycobacterium tuberculosis Infection in IL-12p40-Deficient Mice and Is Not Required for the Development of IL-17-Secreting T Cell Responses

Abstract: Host control of Mycobacterium tuberculosis is dependent on the activation of CD4+ T cells secreting IFN-γ and their recruitment to the site of infection. The development of more efficient vaccines against tuberculosis requires detailed understanding of the induction and maintenance of T cell immunity. Cytokines important for the development of cell-mediated immunity include IL-12 and IL-23, which share the p40 subunit and the IL-12Rβ1 signaling chain. To explore the differential effect of IL-12 and IL-23 durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
2
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 54 publications
(47 reference statements)
7
63
2
2
Order By: Relevance
“…These data are consistent with previous reports that vaccination of mice produces similar numbers of IFN-␥-and IL-17-producing cells in the lungs (12). In addition, it has been reported that IL-17 was not required for the primary response to vaccination; however, it was required for the recall response when the mice were infected with virulent M. tuberculosis (12,48). The contribution of IL-17 to pathology is not clear; however, the absence of IL-23 and IL-17 in mice results in increased lung inflammation (14) after TB infection.…”
Section: Discussionsupporting
confidence: 82%
“…These data are consistent with previous reports that vaccination of mice produces similar numbers of IFN-␥-and IL-17-producing cells in the lungs (12). In addition, it has been reported that IL-17 was not required for the primary response to vaccination; however, it was required for the recall response when the mice were infected with virulent M. tuberculosis (12,48). The contribution of IL-17 to pathology is not clear; however, the absence of IL-23 and IL-17 in mice results in increased lung inflammation (14) after TB infection.…”
Section: Discussionsupporting
confidence: 82%
“…Notably, murine IL-23 can drive the induction of IFN-␥-producing CD4 ϩ T cells in vivo (74). Likewise, IL-12p40 knock-out mice immunized with DNA/IL-23 plasmids, which induced the production of IL-23 but not of IL-12p70 in transfected IL-12p40 knock-out DCs, developed strong Th1 immune responses, rendering the mice partially protected against M. tuberculosis infection (75). Moreover, infection of human DCs with Bordetella pertussis inhibits IL-12p35 production through cAMP induction.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, IL-23 is essential for IL-17 production during infection by Helicobacter pylori, Pneumocystis carinii, and K. pneumoniae (18,30,31). However, for mycobacterial infection, one study showed that IL-23 was required for the IL-17 response to tuberculosis (26), but another demonstrated that IL-23 was dispensable for IL-17 production during infection with M. bovis bacillus Calmette-Guerin (32). We found that IL-23, but not IL-6 or TGF-␤, is required for T cells from persons with M. tuberculosis infection to produce IL-17 in response to mycobacterial Ags.…”
Section: Discussionmentioning
confidence: 99%